A game proposal for teaching math operations to 6th / 9th grade students (Research, Society and Development, 2021)
The purpose of this work is to serve as an aid tool for the teacher, for the students and for the development of the classes, however, we hope that the game is developed in an appropriate way so that it does not harm their performance. The objective of this work is to analyze the possibilities of teaching / learning of mathematical operations from the application of the game "the awakening of mathematics" for 6th and 9th grade students. The work methodology was developed for the students in order to solve such difficulties that some students were presenting during the math classes, developed from cardboard paper, A4 paper in 9x9 square format (9 squares in height and width), containing a total of 81 cells on the board, where the mental calculation of the four mathematical operations is proposed. It was realized that the use of the game should not be applied only as a means of interaction between students, therefore, if the teacher proposes the game as a teaching strategy, he should treat it as a vehicle for building knowledge, creating and experimenting.